The Effect of Classroom Debate on Students' Academic Achievement in Higher Education: an Overview - ghafar, zanyar (MultiTech Publisher, 2024)
The use of classroom debate as an instructional technique is prevalent, particularly in secondary and higher education. There have been several studies examining the effects of classroom discussion in areas such as second language acquisition, philosophical thinking, psychology, and pure science, there is a lack of particular research in the subject of administrative science. Multidisciplinary fields that focus on critical and analytical examination of administrative ideas, management principles, and methods. The review papers covered organisational and leadership theories. Therefore, the study aims is to provide a thorough examination of how classroom debate affects students' academic performance in higher education, in various academic settings, and across all departments and disciplines of study. The research findings indicate classroom debates are beneficial and relevant to many academic subjects because they allow students to think more critically and express creative ideas, which improve their academic performance. A theoretical framework shows a clear connection between student academic success and the advantages of conversation in the classroom.